Financial Distress Prediction in Indonesian Infrastructure Companies Using the Cox Proportional Hazard Model - Mukhlisah, Nurul; Nikmah, Nailiya; Julkawait (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
This study investigates the determinants of financial distress in infrastructure companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024 using survival analysis with the Cox proportional hazard model. The analysis focuses on five firm-level indicators: leverage, profitability, firm size, free cash flow, and sales growth. Survival time until financial distress and event status were constructed to enable longitudinal modeling. Descriptive statistics, Kaplan–Meier estimation, and log-rank tests were employed to explore group differences in survival probabilities, followed by Cox regression to identify key predictors. The results demonstrate that leverage and free cash flow are the most significant determinants of financial distress. A one-standard-deviation increase in leverage raises the hazard by more than twenty-five times, while higher free cash flow reduces the hazard to about 39% of its baseline. Profitability, firm size, and sales growth do not exhibit statistically significant effects. These findings emphasize the dual role of debt burden and liquidity as critical drivers of financial resilience in capital-intensive infrastructure firms. The study provides practical implications for different stakeholders. For managers, it highlights the need to strengthen liquidity management and avoid excessive debt dependence. For investors, leverage and free cash flow indicators serve as reliable early warning signals of potential distress. For regulators, the results underline the importance of monitoring firm-level liquidity and leverage alongside traditional solvency measures to safeguard sectoral stability.